Transcriptome Analysis of NPFR Neurons Reveals a Connection Between Proteome Diversity and Social Behavior - Ryvkin, Julia; Bentzur, Assa; Shmueli, Anat; Tannenbaum, Miriam; Shallom, Omri; Dokarker, Shiran; Benichou, Jennifer I. C.; Levi, Mali; Shohat-Ophir, Galit (Frontiers in Behavioral Neuroscience, 2021)
Social behaviors are mediated by the activity of highly complex neuronal networks, the function of which is shaped by their transcriptomic and proteomic content. Contemporary advances in neurogenetics, genomics, and tools for automated behavior analysis make it possible to functionally connect the transcriptome profile of candidate neurons to their role in regulating behavior. In this study we used Drosophila melanogaster to explore the molecular signature of neurons expressing receptor for neuropeptide F (NPF), the fly homologue of neuropeptide Y (NPY). By comparing the transcription profile of NPFR neurons to those of nine other populations of neurons, we discovered that NPFR neurons exhibit a unique transcriptome, enriched with receptors for various neuropeptides and neuromodulators, as well as with genes known to regulate behavioral processes, such as learning and memory. By manipulating RNA editing and protein ubiquitination programs specifically in NPFR neurons, we demonstrate that the proper expression of their unique transcriptome and proteome is required to suppress male courtship and certain features of social group interaction. Our results highlight the importance of transcriptome and proteome diversity in the regulation of complex behaviors and pave the path for future dissection of the spatiotemporal regulation of genes within highly complex tissues, such as the brain.